2014
DOI: 10.1186/1753-2000-8-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of sexual abuse: improved information is crucial

Abstract: Sexual abuse can lead to long-lasting, even life-long, consequences and is a serious problem on an individual, familial and societal level. Therefore, prevention measures on different levels are a public health issue. Minors as well as adults should be involved in prevention work in order to prevent sexual abuse of minors in a sustainable way. Besides norms, structures and values in society, the respective laws as well as attitudes and structures should be changed and amended in such a way that abusers and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…Identifying the consequences of sexual abuse during childhood is essential, especially in populations for whom sexual violence is considered a public health issue, although substantial progress has been made in Nicaragua in order to address this matter. [15][16][17] Prevalence found for the use of ecstasy (9.1%) in the last 12 months among participants in this study is consistent with the results found in the report Monitoring the Future, by the University of Michigan's Institute for Social Research, although the prevalence of use of cannabis, cocaine, and heroin is lower in our student population than in the population studied in the aforementioned report. 18 After an unstratified analysis of results, we can see a relationship between students' gender and sexual abuse during childhood, as well as the use of cannabis, cocaine, heroin, and ecstasy.…”
Section: Discussionsupporting
confidence: 82%
“…Identifying the consequences of sexual abuse during childhood is essential, especially in populations for whom sexual violence is considered a public health issue, although substantial progress has been made in Nicaragua in order to address this matter. [15][16][17] Prevalence found for the use of ecstasy (9.1%) in the last 12 months among participants in this study is consistent with the results found in the report Monitoring the Future, by the University of Michigan's Institute for Social Research, although the prevalence of use of cannabis, cocaine, and heroin is lower in our student population than in the population studied in the aforementioned report. 18 After an unstratified analysis of results, we can see a relationship between students' gender and sexual abuse during childhood, as well as the use of cannabis, cocaine, heroin, and ecstasy.…”
Section: Discussionsupporting
confidence: 82%
“…Pirminės prevencijos tikslas yra užkirsti kelią seksualinio smurto atsiradimui, šalinant jo priežastis ir rizikos veiksnius. Tai reiškia, kad turi būti kuriama sveika, saugi aplinka ir formuojamos elgesio normos, kurios padėtų išvengti lytinės prievartos atvejų [32]. Prevencijos priemonės apima asmeninį, tarpasmeninį, bendruomenės ir visuomenės lygmenis.…”
Section: Tyrimo Rezultatai Ir Jų Aptarimasunclassified
“…Firstly, not all CSA survivors receive and access existing CSA interventions, making developmental intervention more justified. Secondly, CSA is a significant global challenge in both magnitude and consequence for CSA survivors and their ecological environments (Chitereka 2012;Walsh et al 2015;Zollner et al 2014). Lastly, CSA primary prevention is an attractive option in view of the economic costs of CSA.…”
Section: Social Work Roles At the Macro System Levelmentioning
confidence: 99%